Mystic Experience in Mithraism - BIELAWSKI, KRZYSZTOF (Filozofia Chrześcijańska, 2017)
The paper attempts to describe and interpret mystical experience in the structure of ancient cult of Mithra in his Roman appearance, following the reconstruction of the myth and cultic customs, based on archeological and iconographical evidence as well as on external sources, mainly coming from the works of Christian writers.